Bali Economic, Mobility, Transportation and Hotels to The end of 2021 Tren - DR MUHAMMAD IKHSAN SETIAWAN ST MT; Ronny Durrotun Nasihien; Mohd Adib Mohammad Razi; Wahyu Mulyo Utomo; Muhammad Isradi; Agus Sukoco (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: Based on the Bali Economic Quarterly Development document for the second quarter of 2021 by BPS, the Covid-19 pandemic has become a greater distortion when compared to past events in the Province of Bali. The economic crisis in 1998, the Bali Bombing I in 2002, the Bali Bombing II in 2005, and the eruption of Mount Agung in 2017 can have a lighter impact Design/methodology/approach: Restrictions on transportation routes and calls to stay at home recommended throughout the country should negatively shock the tourism sector Findings: This number experienced a decrease of 7 visits or a decrease of -28.00 percent compared to the previous quarter. The decline in Bali tourism on a quarter to quarter basis is also in line with year on year conditions. Paper type: Research paper